Genotypic diversity of clinical Coxiella burnetii isolates from Portugal based on MST and MLVA-typing - Santos, A.S. (2012)
Genotypic diversity of clinical Coxiella burnetii isolates from Portugal based on MST and MLVA typing. Santos AS, Tilburg JJ, Botelho A, Barahona MJ, Núncio MS, Nabuurs-Franssen MH, Klaassen CH. SourceCentre for Vectors and Infectious Diseases Research Doutor Francisco Cambournac, National Institute of Health Dr. Ricardo Jorge (CEVDI/INSA), Águas de Moura, Portugal. Electronic address: ana.santos@insa.min-saude.pt. Abstract The temporal and spatial diversity of Coxiella burnetii genotypes associated with human and animal disease in Portugal was analysed using a 6-locus multiple-locus variable-number tandem repeat analysis (MLVA) and a 10-locus multi-spacer sequence typing (MST) panel. Fifteen cultured C. burnetii isolates from 13 Q fever patients and a stillborn goat and 6 additional PCR-positive ruminant tissue samples obtained during 2006-2011 were included in this study. Seven MLVA genotypes (types S-Y) were obtained, including 4 new MLVA types (U, V, W, and X), all corresponding to 3 MST profiles (types 4, 8, and 13) previously reported from France and Spain. MLVA types U-Y, all belonging to MST type 4, were found in acute Q fever patients from the districts of Évora, Faro, Lisbon, and Setúbal. Different MLVA types were associated with goats from Castelo Branco district (S) and chronic Q fever patients from both Castelo Branco and Lisboa districts (S and T), matching with MST types 13 and 8, respectively. In conclusion, a genotypic diversity of C. burnetii consistent with a non-outbreak situation was identified. The involvement of different genotypes in acute and chronic Q fever was found, linking one of the chronic genotypes to goats from the eastern region of the country.